Neuromuscular electrical stimulation for stroke rehabilitation: Is spinal plasticity a possible mechanism associated with diminished spasticity? - Motta-Oishi, Anna Amelia P. [UNESP]; Magalhaes, Fernando Henrique; Azevedo, Fabio Micolis de [UNESP] (Churchill Livingstone, 2013)
Although the specific pathophysiological mechanisms underlying the development of spasticity are not fully understood, a large amount of evidence suggests that abnormalities in spinal pathways regulating the stretch reflex may contribute to the hypertonia and hyperreflexia that characterize spasticity. It is quite interesting that neuromuscular electrical stimulation (NMES) has been reported as an efficient treatment for reducing spasticity after stroke while other reports have shown that it promotes neuroplasticity in healthy subjects. The hypothesis addressed in this paper is that plastic effects within some spinal cord pathways may be a possible mechanism associated with the NMES-induced improvements in spasticity. If the hypothesis is proven corrected, the association between plasticity within specific spinal pathways and NMES-induced improvements in spasticity may be used to guide the choice of stimulation parameters to be used in NMES-based stroke rehabilitation protocols. (C) 2013 Elsevier Ltd. All rights reserved.